Development of the DKMQ Element for Buckling Analysis of Shear-deformable Plate Bending. (2017) - Wong, Foek Tjong; Erwin,; Richard, Alexander; Katili, Irwan
Abstract: In this paper the discrete-Kirchhoff Mindlin quadrilateral (DKMQ) element was developed for buckling analysis of plate bending including the shear deformation. In this development the potential energy corresponding to membrane stresses was incorporated in the Hu-Washizu functional. The bilinear approximations for the deflection and normal rotations were used for the membrane stress term in the functional, while the approximations for the remaining terms remain the same as in static analysis. Numerical tests showed that the element has good predictive capability both for thin and thick plates.